Pemanfaatan Media Pembelajaran Canva Pada Pelajaran IPAS di Kelas III SDI Mutiara Islam Al Ittiba - Nurwanaliyanti Nurwanaliyanti; Anggra Prima; Jumrianah Jumrianah (Global Education Journal, 2026)
This study aimed to describe the utilization of Canva as a learning medium in IPAS instruction and to identify the supporting and inhibiting factors in its implementation among third-grade students at SDI Mutiara Islam Al Ittiba’ Sangatta Utara. A qualitative descriptive field research design was employed, with data collected through classroom observation, semi-structured interviews with the vice principal for curriculum, two homeroom teachers, and selected students, as well as documentation of learning materials. Data were analyzed using the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing, while data trustworthiness was ensured through source, technique, and time triangulation. The findings revealed that Canva was utilized across three main stages: planning, where teachers designed slides, student worksheets (LKPD), and happy notes tailored to students’ characteristics; implementation, where it served as a visual and interactive tool to present material and facilitate discussion; and evaluation, where it supported feedback through attractive notes. Supporting factors included adequate technological facilities, the user-friendly nature of Canva, school policy support, and students’ enthusiasm. In contrast, inhibiting factors comprised limited access to Canva Edu, unstable internet connections, insufficient supporting devices, time constraints in media preparation, and the tendency to use templates without sufficient pedagogical adaptation. Teachers addressed these challenges through adaptive strategies such as preparing backup media, downloading designs in advance, simplifying visual layouts. The study concludes that Canva effectively enhanced the concreteness and engagement of IPAS learning, although its optimal utilization requires stronger institutional support in infrastructure and continuous teacher professional development.